THE EFFECTIVENESS OF USING PRE-QUESTIONING TECHNIQUE IN READING COMPREHENSION ON A NARRATIVE TEXT - Maliyanti, Mamie; Salam, Urai; Sumarni, Sumarni (Universitas Tanjungpura, 2024)
This research aimed to identify the effectiveness of empowering PreQuestion techniques and identified the size of the effectiveness on students' achievement in understanding in reading activity. This research applied a pre-experimental approach. This research involved all students in class VIII of SMPN 5 Salatiga, Sambas Regency, totaling 28 students. Data was collected through the use of reading and multiple choice tests. The research results showed that the pretest results were 54.64 and the post-test results were 72.67. It means based on that data showed the post-test average score higher than pre-test average score Besides, the T-test results obtained were relatively high, namely 21.98, while the T-critical obtained were 2.051 because T-test T-count, it showed that the Alternative Hypothesis (Ha) was accepted and the Null Hypothesis (Ho) was rejected. Other findings showed that the effect size is classified as good, namely 0.77 and is in the medium category. The general conclution showed that the Pre-Questioning technique was effective to apply and increasing students' reading comprehension